Distance and Rotational Speed Analysis of Coaxial Rotors for UTHM C-Drone - Che Umar, Che Muhammad Ikram; Zulkafli, Mohd Fadhli (Progress in Aerospace and Aviation Technology, 2021)
The prototype of UTHM C-Drone use a coaxial hexacopter concept for its propulsion system. A coaxial rotors consists of two motor and two propellers mounted above each other and aligned in relation to their axis of rotation. The propellers are based on the T-Motor U15XXL KV29 model used in UTHM C-Drone. The distance between the two propellers is usually relative to the radius of the propeller or can be lesser. The objectives for this study are to investigate the effect of distance between upper and lower propeller in a coaxial rotors system and the effect of rotational speed. This study is important to ensure the C-Drone power efficient and capable to lift 180 kg payload. The CAD model of the propeller and coaxial rotors system were designed based on the specification from T-Motor company by Solidworks software and the flow simulations were conducted using Solidworks Flow Simulation module. The total of six CAD models; one for a single propeller and five for coaxial rotors with five difference of distance cases were constructed. For each model, the total thrust was tested from 50% throttle power up to the 90% throttle power. It was found that the coaxial rotors system can generate more thrust than a single propeller but less than double. It was also found that if the lower propeller rotates faster than the upper propeller, the increment of total thrust is very small. However, if the upper propeller rotates faster than the lower propeller, the total thrust increase significantly. For the case of faster upper propeller, as the higher the throttle applied, the thrust increment ratio will decrease, and the efficiency of the thrust produced will be affected. In addition, for same rotation speed, the thrust generated was lesser when both propellers rotate in a same direction compared to when each propeller rotates in the opposite directions of each other.